Impact of social influence on whatsApp’s organizational usage within Malaysian HEI’s - Mohsin Ali, Rana; Mahomed, Anuar Shah Bali; Raja Yusof, Raja Nerina (Science and Engineering Research Support Society, 2020)
The last decade has shown extensive growth of IT in communication system, mainly because of the progress of mobile communication technologies because of which the flow of information and messages has become faster and instant. These developments in mobile communication technologies have motivated many to adopt different platforms which have offered new useful and appealing communication technologies. The most famousof these platforms in many countries is WhatsApp, which has seen enormous hike in its adoption rate since it was invented in year 2009. Out of many factors that affect adoption of a new technology by a person or by an organization, researchers suggested social influence as one of the most important ones. This research studies the impact of social influence on WhatsApp’s official usage within Malaysian universities. Using quantitative survey technique and analyzing the data in SMART PLS-SEM, all the hypothesized statements were confirmed and the findings show a strong relationship between constructs. Lastly, research limitations and directions for future research have been discussed.